On Universal Currency Hedges - Adler, Michael; Prasad, Bhaskar (Journal of Financial and Quantitative Analysis, 1992)
This paper identifies five universal currency hedge ratio (UHR) definitions. These are hedge positions in foreign bonds, stated as a fraction of national or global equity portfolios, that are the same for all investors, regardless of nationality. The first three involve the total demand for foreign bonds and depend on equities not being held for hedging purposes. The last two are associated with variance-minimizing regression hedges. These hold, in general, but are designed exclusively for hedging other traded asset positions. Jensen's inequality makes the choice of measurement currency irrelevant and makes the HRs universal without affecting their values.